Systematic Literature Review: Utilization of e-Learning in Indonesian Higher Education - Agustia, Natasya Citra; Nagima Zhumakadyrova (NAJAHA, 2025)
This research is an empirical study of literature reviews published in journals from 2015-2022 to identify the methods, challenges, and benefits of e-Learning in Indonesian higher education. The results show that the use of e-Learning in Indonesian higher education has provided relevant benefits with the current technological advancements. Some benefits of e-Learning are: providing flexibility in the learning process, giving students the freedom to access learning materials, providing financial savings, providing access speed that is tailored to students' learning speed, applying current technology in the learning process, using current learning platforms, and reaching a wider area with e-Learning speed. However, the use of e-Learning is not without challenges, such as: limited internet network and electricity flow, lack of users (lecturers and students) in using current technology, not considering the differences in the abilities of each student, limitations in communication facilities for clarifying lesson material, limited material that can use e-Learning, and not all students are capable of using computers well.